2021
DOI: 10.2196/preprints.27818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Physical and Mental Health in China and Spain: Cross-sectional Study (Preprint)

Abstract: BACKGROUND The differences between physical and mental health across continents during the Coronavirus Disease 2019 (COVID-19) pandemic was unknown. OBJECTIVE This study compared the levels of impact of COVID-19 and mental health between people from Spain and China, and to correlate mental health parameters with variables relating to symptoms similar to COVID-19, COVID-19 knowledge and precauti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 8 publications
2
17
2
2
Order By: Relevance
“…From the independent sample t-test it is clear that the level of CAS among women respondents are higher than the male respondents during the COVID-19 pandemic, which is supported by previous studies [23][24][25][26]. Younger and less educated group of participants are experiencing higher anxiety, which is also supported by the previous work of Taylor et al [25] Health anxiety is a function of how likely and how severe society perceives the illness.…”
Section: Discussionsupporting
confidence: 71%
“…From the independent sample t-test it is clear that the level of CAS among women respondents are higher than the male respondents during the COVID-19 pandemic, which is supported by previous studies [23][24][25][26]. Younger and less educated group of participants are experiencing higher anxiety, which is also supported by the previous work of Taylor et al [25] Health anxiety is a function of how likely and how severe society perceives the illness.…”
Section: Discussionsupporting
confidence: 71%
“…The COVID-19 pandemic affects both the physical and mental health of individuals, 9,26,27 with healthcare workers being particularly subjected to various stressors, which may lead to higher levels of emotional distress. 4 Shacham, et al 28 (2020) found an elevated risk of psychological distress in 11.5% (n=39) of the dentists evaluated in Israel during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants washed their hands with soap after touching contaminated objects, closed their mouths during sneezing or coughing, and wore a mask regardless of symptoms patients had. Very beginning of Covid-19 outbreak in China, the internet had become the main information channel (93.5%) (12).…”
Section: Discussionmentioning
confidence: 99%